Impact of Mediation Techniques on Conflict Resolution Outcomes in Workplace Disputes in Ghana - Allotey, John (European Journal of Conflict Management, 2024)
Purpose: The aim of the study was to assess the impact of mediation techniques on conflict resolution outcomes in workplace disputes in Ghana. Materials and Methods: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study indicate that effective mediation significantly enhances the resolution of workplace conflicts by fostering communication, understanding, and cooperation among disputing parties. Techniques such as active listening, where mediators attentively listen to all parties involved, and reframing, which involves presenting issues in a more constructive manner, are particularly impactful. These techniques help to de-escalate tensions and enable participants to view the conflict from different perspectives, leading to more collaborative problem-solving. Moreover, the use of interest-based mediation, which focuses on identifying the underlying interests and needs of the parties rather than their positions, has been shown to yield more sustainable and satisfactory outcomes. Implications to Theory, Practice and Policy: Social exchange theory, transactional analysis and systemic approach may be used to anchor future studies on assessing the impact of mediation techniques on conflict resolution outcomes in workplace disputes in Ghana. Invest in comprehensive mediator training programs that emphasize a diverse range of mediation techniques, including active listening, empathy-building, reframing narratives, and promoting participant autonomy. Develop guidelines and standards for the use of online mediation platforms, considering factors such as data security, accessibility, technological literacy, and equitable access to digital resources.